Polypeptide Modulators of TRPV1 Produce Analgesia without Hyperthermia - Andreev, Yaroslav A. (MDPI, 2013)
Transient receptor potential vanilloid 1 receptors (TRPV1) play a significant physiological role. The study of novel TRPV1 agonists and antagonists is essential. Here, we report on the characterization of polypeptide antagonists of TRPV1 based on in vitro and in vivo experiments. We evaluated the ability of APHC1 and APHC3 to inhibit TRPV1 using the whole-cell patch clamp approach and single cell Ca(2+) imaging. In vivo tests were performed to assess the biological effects of APHC1 and APHC3 on temperature sensation, inflammation and core body temperature. In the electrophysiological study, both polypeptides partially blocked the capsaicin-induced response of TRPV1, but only APHC3 inhibited acid-induced (pH 5.5) activation of the receptor. APHC1 and APHC3 showed significant antinociceptive and analgesic activity in vivo at reasonable doses (0.01–0.1 mg/kg) and did not cause hyperthermia. Intravenous administration of these polypeptides prolonged hot-plate latency, blocked capsaicin- and formalin-induced behavior, reversed CFA-induced hyperalgesia and produced hypothermia. Notably, APHC3’s ability to inhibit the low pH-induced activation of TRPV1 resulted in a reduced behavioural response in the acetic acid-induced writhing test, whereas APHC1 was much less effective. The polypeptides APHC1 and APHC3 could be referred to as a new class of TRPV1 modulators that produce a significant analgesic effect without hyperthermia.